2011
DOI: 10.1088/0029-5515/51/11/113008
|View full text |Cite
|
Sign up to set email alerts
|

Control of magnetic islands in the STOR-M tokamak using resonant helical fields

Abstract: The resonant interaction between magnetohydrodynamic (MHD) instability modes and the externally applied helical magnetic field is demonstrated in the Saskatchewan Torus-Modified (STOR-M) tokamak. The study is conducted both numerically and experimentally using a 2D MHD equilibrium code in the former and an (l = 2, n = 1) helical coil carrying a short current pulse in the latter. It is shown numerically that the resonant helical current can efficiently suppress the magnetic islands resonating on the (m = 2, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Another effect of rotation modulation by F em and F vs is that the island spends more time in the deceleration phase (0 < Φ < π) than in the acceleration phase (π < Φ < 2π), resulting in a net braking effect, that is why rotation reduction is usually observed associated with mode stabilization. 1,8,9 Based on the above understanding and numerical studies in Ref. 9, we conclude that the applied RMPs contributes a net and dominant stabilizing effect on TM, whether the TM can be stabilized depends on the plasma rotation and other plasma parameters.…”
Section: Discussion and Summarymentioning
confidence: 61%
See 2 more Smart Citations
“…Another effect of rotation modulation by F em and F vs is that the island spends more time in the deceleration phase (0 < Φ < π) than in the acceleration phase (π < Φ < 2π), resulting in a net braking effect, that is why rotation reduction is usually observed associated with mode stabilization. 1,8,9 Based on the above understanding and numerical studies in Ref. 9, we conclude that the applied RMPs contributes a net and dominant stabilizing effect on TM, whether the TM can be stabilized depends on the plasma rotation and other plasma parameters.…”
Section: Discussion and Summarymentioning
confidence: 61%
“…3 Since the first RMPs experiment on PULSATOR, 4 many experiments related to RMPs have been carried out. 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The RMPs related experiments covers a broad spectrum of physics issues including the effect of RMPs on tearing mode (TM) dynamics, 1, 4-10 error field, 11,12 particle transport, 13,14 and mitigation or suppression of edge localized modes (ELMs). [15][16][17][18] One of the results is that RMPs with moderate amplitude can suppress Mirnov oscillations effectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the precursor MHD instability before disruption is verified to be the tearing mode (TM) [1], hence it is important to control the precursor TM for the disruption mitigation/avoidance. Previous experimental studies showed that RMPs can suppress rotating TM effectively, accompanied by a plasma rotation reduction [14][15][16][17]. Theoretical analysis developed by Fitzpatrick [18,19] reveals that the applied RMPs contribute a net stabilizing and braking effect on the TM and plasma rotation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Externally exerted dynamic resonant magnetic perturbation (DRMP) is an effective method used to control the TM [3][4][5][6][7][8]. On the J-TEXT tokamak, the phenomenon of the TM locking to the constant frequency DRMP has been observed [6].…”
Section: Introductionmentioning
confidence: 99%